(untitled) (Hekima Review, 1994)
After the publication of the Lineamenta in 1990, and during the four years of preparation that followed before the actual celebration of the Synod, there was a tendency to speak of 'proclamation', 'inculturation', 'dialogue', 'justice and peace' and 'means of social communication' as five topics or themes of the Synod. It was known that they were in fact aspects of evangelisation but it was not always easy to preserve the unity of the theme in the diversity of its aspects